Evaluation of Er:YAG lasers on pain perception in pediatric patients during caries removal: a split-mouth study - Emre Korkut; Onur Gezgin; Hazal Özer; Yağmur Şener (Gazi University, 2018)
Objective: Fear and anxiety is a major problem in the treatment of pediatric patients. The pain that occurs during the use of caries removal instruments has a strong potential of triggering dental anxiety and fear in most children and adults. This study aimed to evaluate and compare the pain perceptions of children who underwent caries removal via an Er:YAG laser and traditional rotary instruments. Materials and Method: Occlusal caries was removed from the permanent molar teeth of 120 pediatric patients who referred to the Department of Pediatric Dentistry, Faculty of Dentistry, Necmettin Erbakan University, using an Er:YAG laser and high- and low-speed rotary instruments. All restorative procedures were performed by one clinician. The participant children were asked to choose a value or figure from the Wong-Baker FACES Pain Rating Scale, and the data were analyzed using the Wilcoxon test (α=0.05). Results: A statistically significant difference was found between the groups (p<0.05). In the Er:YAG laser group, 20.83% of the participants, and in the conventional group, 6.66% of the participants selected the option 'no hurt'. The option 'hurts worst' was selected in neither of the groups. Conclusion: The use of Er:YAG laser for caries removal causes less or no pain during the operations, compared to traditional rotary instruments. Therefore, it can be argued that Er:YAG laser is a more comfortable and acceptable alternative for pediatric patients.